2023
DOI: 10.1186/s12872-023-03106-0
|View full text |Cite
|
Sign up to set email alerts
|

Causes and treatment strategies of unilateral leaflet escape of bileaflet mechanical prosthetic heart valves after surgery: a case series

Abstract: Background During the eleven years from 2010 to 2021, preliminary statistics have shown that Fuwai Hospital completed 23,571 mechanical valve replacements for various types of valves, and 1139 mechanical valve replacements were performed in Guangyuan First People's Hospital. Only two patients developed valve leaflet escape, so valve leaflet escape is a rare postoperative complication. Case presentation In 2010 and 2021, two patients were selected a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Prosthetic valve complications, both early and late, encompass PPM, geometric mismatch, dehiscence, primary failure, thrombosis, thromboembolism, pannus formation, pseudoaneurysm formation, endocarditis, and hemolysis. [4] A study by Wang et al [2] reported that Fuwai Hospital and Guangyuan First People's Hospital conducted 24,710 valve replacements and 3264 first-time valve replacements over a decade. Among these cases, only 2 instances of unilateral leaflet escape were identified, constituting 0.06% of second-stage valve replacement cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prosthetic valve complications, both early and late, encompass PPM, geometric mismatch, dehiscence, primary failure, thrombosis, thromboembolism, pannus formation, pseudoaneurysm formation, endocarditis, and hemolysis. [4] A study by Wang et al [2] reported that Fuwai Hospital and Guangyuan First People's Hospital conducted 24,710 valve replacements and 3264 first-time valve replacements over a decade. Among these cases, only 2 instances of unilateral leaflet escape were identified, constituting 0.06% of second-stage valve replacement cases.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Since its introduction in 1980, the bileaflet mechanical prosthetic heart valve has emerged as the predominant product due to its exceptional performance. [2] Despite their increased durability compared to bioprostheses, mechanical prosthetic heart valves may encounter dysfunction attributed to 4 primary phenomena: thrombosis; fibrotic pannus ingrowth; degeneration; and endocarditis. [3] Although complete valve dislodgement remains unreported, the primary causative factor is likely the deterioration and breakage of sutures.…”
Section: Introductionmentioning
confidence: 99%
“…The sewing ring is used to attach and fix the orifice ring to the heart tissue [14]. Three classifications of mechanical heart valve available which are caged-ball, single-tilting disk, and bileaflet-tilting disk valves [10,15]. The bileaflet valve is found to be the most common implanted mechanical valve that introduced to provide a better blood flow, low jet velocity, small pressure drops, and large effective orifice area [16].…”
Section: Introductionmentioning
confidence: 99%